AGE-RELATED CLINICAL AND HEMODYNAMIC FEATURES OF THE EARLY POSTOPERATIVE PERIOD IN CHILDREN AFTER CONGENITAL HEART DEFECT REPAIR - Kashtalian, Mykhailo; Melnychenko, Maryna; Buzovskyi, Volodymyr; Kvasnevskyi, Yevhen (Eastern Ukrainian Medical Journal, 2026)
Introduction. Congenital heart defects (CHDs) remain a major cause of pediatric cardiac surgery worldwide. Despite advances in surgical techniques and perioperative care, the early postoperative period remains variable and may depend on patient age, CHD characteristics, and postoperative adaptation.Objective. To evaluate age-related features of the early postoperative period in children after surgical correction of congenital heart defects and their association with CHD structure and postoperative adaptation.Materials and Methods. This retrospective single-center study included 206 children aged 0–14 years who underwent CHD repair between 2015 and 2024. Patients were divided into five age groups: neonates, infants, children aged 1–3 years, 3–7 years, and 7–14 years. Clinical, laboratory, and echocardiographic parameters were assessed during the early postoperative period. Statistical analysis included descriptive statistics, one-way ANOVA, and χ² testing.Results. Significant age-related differences were observed in hospitalization duration, heart rate, extracardiac comorbidity, and CHD structure. Neonates had the longest hospital stay, the highest prevalence of extracardiac comorbidity, and the greatest proportion of complex CHDs. Laboratory parameters were generally comparable between age groups and reflected a common postoperative inflammatory response. Echocardiography revealed more frequent right ventricular dilatation and pulmonary hypertension in younger patients. The distribution of CHD types differed significantly across age groups and appeared to influence postoperative adaptation. The observed differences were associated not only with age but also with CHD complexity, baseline clinical status, and perioperative factors.Conclusions. The early postoperative period after CHD repair demonstrates clinically relevant age-related characteristics. Neonates represent the most vulnerable patient group, whereas older children generally show a more stable postoperative course. These findings should be interpreted as reflecting the combined influence of age, CHD structure, extracardiac comorbidity, and postoperative adaptation rather than an independent effect of age alone.